Prognostic value of O‐6‐methylguanine‐DNA methyltransferase loss in salivary gland carcinomas. Issue 9 (27th November 2013) - Scesnaite, Asta; Jarmalaite, Sonata; Mueller, Maximillian; Agaimy, Abbas; Zenk, Johannes; Hartmann, Arndt; Iro, Heinrich; Peters, Brigitte; Schwarz, Stephan; Schneider–Stock, Regine
Abstract Background The purpose of this study was to determine the prognostic value of O‐6‐methylguanine‐DNA methyltransferase (MGMT) inactivation in a group of 286 patients with salivary gland carcinoma and matched histologically normal tissues. Methods MGMT promoter methylation was studied in 36 patients with salivary gland carcinoma and 19 histologically matched normal tissues by pyrosequencing. MGMT protein expression was examined in 286 patients with salivary gland carcinomas and histologically matched normal tissues by immunohistochemistry on tissue microarrays. The results were correlated to demographic, clinicopathologic parameters, and disease follow‐up data. Results MGMT hypermethylation was significantly (p = .021) associated with the protein loss. MGMT loss was found in 39.2% of salivary gland carcinomas and was predominant in aggressive tumors (poorly differentiated, grade III, regional lymph node involved). MGMT loss significantly (p = .004) predicted poor clinical outcome of salivary gland carcinomas and defined high‐risk subgroups in clinically favorable tumor groups. Conclusion We suggest that immunohistochemical evaluation of nuclear MGMT protein might serve as a tool for the prediction of overall survival in patients with salivary gland carcinoma. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1258–1267, 2014